The ceramic industry in Thailand - W. Schulle (2018)
A word of introduction to Thailand is followed by a brief overview of the history of ceramics in the country. Five key manufacturing centres and some specialised production sites are then described. The paper goes on to look at the main deposits of ceramic raw materials in Thailand. Research and training centres in the ceramic field are detailed, and in conclusion the author provides a short assessment of the current state of the ceramic industry in Thailand.